Neurological Complications following Surgical Treatments of the Lower Molars - Antonio Mancini; Angelo Michele Inchingolo; Marco Di Blasio; Elisabetta de Ruvo; Angela Di Noia; Laura Ferrante; Gaetano Del Vecchio; Andrea Palermo; Francesco Inchingolo; Alessio Danilo Inchingolo; Gianna Dipalma (International Journal of Dentistry)
Aim. The current review aims to explore postoperative neurological complications in third molar extractive surgery. Materials and Methods. The PRISMA protocols were followed when conducting this review. We found a total of 2,250 articles that matched our topic using the Boolean keywords, mandibular nerve complications AND oral surgery, from PubMed (1,083), Scopus (435), and Web of Science (732), with the filters of English language articles, time range January 1, 2003, to September 30, 2023, and human studies. After 762 duplicates were eliminated, there remained 1,488 articles. Eleven final articles were deemed of the highest relevance to our topic by eliminating articles in animals, non-English language, reviews, meta-analysis, and off-topic. A potential risk in the third molar extraction was temporary loss of sensibility often caused by mild compression or irritation of the mandibular nerve. This typically resolves within weeks or months, but in severe cases, recovery might take longer. Permanent loss of sensation can occur, indicating significant nerve damage and lasting effects on touch, temperature, or pain perception. Conclusions. Various treatments exist for nerve damage, including low-level laser therapy, pain management medications, or physical therapy. While these therapies may improve neurosensory impairment, patients often report a decline in their quality of life.